A case of craniopharyngioma presenting as rapidly progressive dementia - Das, Soumitra (Indian J Psychiatry, 2018)
Rapidly progressive dementia (RPD) is generally obvious to family member but often difficult for physicians to pinpoint the underlying pathology. Some common causes, such as prion's disease, Alzheimer's disease, central nervous system vasculitis, or infection, might present with disease-specific signs or symptoms where many etiologies do not produce such warning signs. Here, we are presenting a case who attended the psychiatric clinic for decreased motivation to do work, easy fatigability, infrequent falls, recent memory impairment, increased appetite, polydipsia and polyuria, and provisionally diagnosed with RPD. Magnetic resonance imaging revealed solid cystic lesion in suprasellar location involving hypothalamus, optic chiasma, and optic tracts, compressing the floor of the third ventricle suggestive of craniopharyngioma which is one of the very few reports in literature.